Propuesta arquitectónica de un mercado minorista enfocado en la reestructuración de la Feria Amazonas de la ciudad de San Gabriel-Carchi - Benavides Rodriguez, Jordy Alexander (2024)
This degree work is developed from the investigation and analysis of the commerce and supply system of the city of San Gabriel, Carchi. This dynamic constitutes the most relevant commercial axis at the canton, because it is responsible for supplying the urban and rural parishes, through the existing fairs and markets that are: Feria San José, Mercado Central Jesús del Gran Poder and Feria Amazonas. The latter is the largest fair and the most popular within San Gabriel due to the diversity of fresh products, textiles, footwear and various objects it offers. However, since its inception it has taken over Simón Bolívar Street with tents and precarious infrastructure, without guarantees of safety and health for merchants and consumers, causing the deterioration of public space. It is for this reason that the conditions in which this fair takes place become a real problem where the number of merchants increases and the lack of a space designated for the development of this type of activities is evident. In this sense, the work is based on the application of different methodologies and research instruments that allow us to understand its dynamics and the richness that commerce offers, due to guarantee its correct functioning it is necessary to take into account its dynamic, colorful and open to the public. Therefore, the proposal of this work aims to restructure the commercial dynamics that take place on Feria Amazonas through a retail market that does not enclose merchants within a space, but rather prioritizes the flexibility of commerce through market squares that generate fluid routes and invite the user to explore the space to carry out various activities and exchange experiences, becoming a lively, useful public space and at the same time improving the health conditions and order in which the spply system is managed.